A New Bifidobacteria Expression SysTem (BEST) to Produce and Deliver Interleukin-10 in Bifidobacterium bifidum - Mauras, Aurélie; Chain, Florian; Faucheux, Aurélie; Ruffié, Pauline; Gontier, Sophie; Ryffel, Bernhard; Butel, Marie-José; Langella, Philippe; Bermúdez-Humarán, Luis G.; Waligora-Dupriet, Anne-Judith (Frontiers in Microbiology, 2018)
In the last years there has been a growing interest in the use of genetically modified bacteria to deliver molecules of therapeutic concern at mucosal surfaces. Due to well-recognized probiotic properties of some strains, bifidobacteria represent excellent candidates for the development of live vehicles to produce and deliver heterologous proteins. However, very few studies have considered this genus because of its complexity to be genetically manipulated. In this study, we report the development of a new Bifidobacteria Expression SysTem (BEST) allowing the production of proteins of medical interest in Bifidobacterium bifidum. This system is based on the broad host range plasmid pWV01, a stress-inducible promoter, and two different signal peptides (SPs): SPExp4 issued from Lactococcus lactis and SPBL1181 issued from Bifidobacterium longum. The functionality of BEST system was validated by cloning murine interleukin-10 (IL-10) and establishing the resulting plasmids (i.e. pBESTExp4:IL-10 and pBESTBL1181:IL-10) in B. bifidum. We demonstrated in vitro that a recombinant strain of B. bifidum BS42 harboring pBESTBL1181:IL-10 plasmid efficiently secreted IL-10 and this secretion was significantly higher (7-fold) than its counterpart B. bifidum BS42 harboring pBESTExp4:IL-10 plasmid. Finally, we validated in vivo that recombinant B. bifidum strains producing IL-10 using BEST system efficiently delivered this cytokine at mucosal surfaces and exhibit beneficial effects in a murine model of low-grade intestinal inflammation.